Size effect induced activity enhancement and anti-photocorrosion of reduced graphene oxide/ZnO composites for degradation of organic dyes and reduction of Cr(VI) in water - Zhang, Yanhui; Chen, Zhang; Liu, Siqi; Xu, Yi-Jun (Applied catalysis. B, Environmental, 2013)
RGO/ZnO composites with different size of ZnO particles have been fabricated via a one-step facile solvothermal method. The photocatalytic activities of these composites have been investigated toward dye degradation and Cr (IV) reduction in an aqueous phase. It is found that ZnO-S1, with relatively small particles size distribution, is able to hybridize with RGO sheet more efficiently than that for the hybridization of ZnO-S2, with large particles size distribution, with RGO sheet. Such a particle size effect leads the more efficient interfacial interaction between ZnO-S1 and RGO, which leads to both the enhanced photoactivity and the significantly decreased photocorrosion. In addition, we have also used the radicals scavengers technique to study the role of photoactive species involved in the photocatalytic degradation of dye and reduction of Cr (VI). •Particles size of ZnO strongly influences the photocatalytic performance of RGO/ZnO composites.•The photocorrosion of ZnO is inhibited by the hybridization of RGO with ZnO in an appropriate manner.•Possible photocatalytic reaction mechanism over RGO/ZnO composites has been studied. The composites of reduced graphene oxide/ZnO (RGO/ZnO) with different particles size of ZnO have been prepared via a facile solvothermal reaction of graphene oxide (GO) and ZnO in an ethanol-water solvent. It is found that the RGO/ZnO-S1 composite with ZnO particle size of 20–100nm exhibits the enhanced photoactivity toward degradation of organic dyes and reduction of heavy metal ions Cr(VI) in water as compared to the bare ZnO-S1 sample under UV light irradiation. However, the RGO/ZnO-S2 composite with ZnO particle size of 50–500nm shows decreased photoactivity as compared to bare ZnO-S2. The recycled photoactivity testing shows that, for RGO/ZnO-S1, the photocorrosion of ZnO-S1 is efficiently inhibited by the hybridization with RGO whereas the case is not for RGO/ZnO-S2. A collection of characterization techniques disclose that the smaller particles size for RGO/ZnO-S1 than that for RGO/ZnO-S2 leads to a more interfacial contact and a chemical bonding between RGO and ZnO-S1, thereby resulting in enhanced photoactivity and efficient anti-photocorrosion as observed for RGO/ZnO-S1. Furthermore, the possible reaction mechanism for degradation of dyes and reduction of Cr(VI) over RGO/ZnO-S1 has also been studied. Our results suggest that the semiconductor particles size has an important effect on the photocatalytic performance of RGO/semiconductor composites photocatalysts. The hybridization of RGO with ZnO in an appropriate manner is able to significantly inhibit the well-known photocorrosion of semiconductor ZnO. It is anticipated that this work would enrich the applications of RGO/semiconductor photocatalysts in environment purification.